Response Characteristics of Dynamic Torque for Wet Clutch Engagement: A Numerical and Experimental Study - Zhigang Zhang; Ling Zou; Hang Liu; Jin Feng; Zhige Chen (Shock and Vibration)
To determine the factors affecting the dynamic transmitted torque response characteristics of the wet clutch, the oil film pressure, the asperity contact pressure, the applied pressure, and the dynamic transmitted torque model were established, using the fourth-order Runge–Kutta numerical method to couple the oil film thickness and the speed difference to obtain the change curve of the joint pressure and the transmitted torque. The established model was used to study the influence of the pressure hysteresis time, lubricant viscosity, friction lining permeability, friction pair equivalent elastic modulus, and surface combined roughness RMS on the dynamic transmitted torque response during the wet clutch engagement. The results indicate that the longer the pressure hysteresis time, the smaller the permeability of the friction lining, the smaller the equivalent elastic modulus, the greater surface combined roughness RMS, the more delayed the response of the transmitted torque, and the smaller the level of jerk of the wet clutch engagement. Also, the lower the lubricant viscosity, the greater the permeability of the friction lining, and the smaller the equivalent elastic modulus is and the greater surface combined roughness RMS is, the more sensitive the transmitted torque response is to pressure response changes.